2011
DOI: 10.1111/j.1530-0277.2011.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcoholism and Continued Abstinence on Brain Volumes in Both Genders

Abstract: Our study confirms widespread cerebral volume loss in recently detoxified alcoholics. The effects of alcohol dependence seem to have equally adverse effects on brain morphometry in males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 29 publications
17
109
2
3
Order By: Relevance
“…However, this topic remains controversial (for a review, see Hommer, 2003). A recent voxel-based morphometry study reported no significant gender  diagnosis interactions for global and regional (including insula) brain volumes, or voxel-based morphometry results (Demirakca et al, 2011). Similarly, our analysis did not find differential effects of gender on the insula volume in ADPs versus healthy volunteers.…”
Section: Limitationssupporting
confidence: 31%
See 2 more Smart Citations
“…However, this topic remains controversial (for a review, see Hommer, 2003). A recent voxel-based morphometry study reported no significant gender  diagnosis interactions for global and regional (including insula) brain volumes, or voxel-based morphometry results (Demirakca et al, 2011). Similarly, our analysis did not find differential effects of gender on the insula volume in ADPs versus healthy volunteers.…”
Section: Limitationssupporting
confidence: 31%
“…In our primary analysis, we excluded these participants and found a significant difference in insula and amygdala volumes between healthy volunteers and ADPs. However, previous studies have shown that a highly significant portion of insula volume is recovered after 3 months of abstinence from alcohol (Demirakca et al, 2011). Therefore, we included these four healthy volunteers in the reanalysis to increase the power of the outcome.…”
Section: Insular Cortex Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies, also, have shown that myelin sheaths are affected by chronic alcohol consumption [55] and white matter loss has been reported in several studies of alcoholic patients [12,21,22,56].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, abstinent alcohol-dependent individuals show a partial regeneration of brain volume changes, even during early abstinence [8][9][10] . Brain volume regeneration appears to be greater during the first several weeks compared to continued long-term abstinence [10,11] .…”
Section: Introductionmentioning
confidence: 99%